Cyber Espionage Policy and Regulation: A Comparative Analysis of Indonesia and Germany - Susila, Muh Endriyo; Salim, Andi Agus (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2024)
This study explores the policy and regulatory frameworks concerning cyber espionage within Indonesia and Germany. Given the considerable threats cyber espionage poses to national security and economic interests, it is crucial for nations to formulate thorough strategies to mitigate such risks. Through a comparative analysis of Indonesia and Germany—two countries with distinct geopolitical stances and methodologies regarding cybersecurity and espionage—the research delves into the legal, political, and technological factors influencing their cyber espionage policies. The methodology includes a comprehensive review of legislative measures, governmental strategies, and the response of institutions to cyber espionage in both nations. The objective is to discern the similarities, differences, and effectiveness of the policies and regulations of these countries. This comparison sheds light on the adequacy of Indonesian legislation in combating cybercrime, especially cyber espionage. The study reveals that Indonesia's legal infrastructure for cybercrime is markedly underdeveloped compared to Germany's, where stringent and well-articulated regulations are in place, facilitating precise and efficient management of cyber issues. Thus, the study underscores an urgent need for Indonesia to reform its cybercrime laws, focusing on cyber espionage, among other cyber threats, while continuing to enhance the quality of its human resources.DOI: https://doi.org/10.22304/pjih.v11n1.a6